Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/17453674.2021.1968727
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body mass index and age on day-of-surgery discharge, prolonged admission, and 90-day readmission after fast-track unicompartmental knee arthroplasty

Abstract: Background and purpose — The indications for unicompartmental knee arthroplasty (UKA) have become less restrictive and, today, high age and high BMI are not considered contraindications by many surgeons. While the influence of these patient characteristics on total knee arthroplasty is well documented, evidence on UKA is lacking. We investigated the effect of BMI and age on day of surgery (DOS) discharge, prolonged admission, and 90-day readmission following UKA surgery. Patients and methods — This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…42 However, in a recent study by Jensen et al, (n=3,897), they found that a high BMI was associated with an increased 90-day readmission rate after UKA surgery. 43 A large database study by Kandil et al,(n=15,770) also showed a significant increased risk of major and minor complications within 90 days in both obese (BMI 30 to 39.9; OR 2.3) and morbidly obese (BMI >39.9; OR 3.2) patients. 44 This study is limited by the lack of knowledge of the outcomes in patients who had incomplete forms.…”
Section: Discussionmentioning
confidence: 93%
“…42 However, in a recent study by Jensen et al, (n=3,897), they found that a high BMI was associated with an increased 90-day readmission rate after UKA surgery. 43 A large database study by Kandil et al,(n=15,770) also showed a significant increased risk of major and minor complications within 90 days in both obese (BMI 30 to 39.9; OR 2.3) and morbidly obese (BMI >39.9; OR 3.2) patients. 44 This study is limited by the lack of knowledge of the outcomes in patients who had incomplete forms.…”
Section: Discussionmentioning
confidence: 93%
“…Many of these orthopedic studies have shown obesity and older age, among other risk factors, to be associated with postsurgical readmission. 20 , 21 , 22 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Geriatric conditions are associated with adverse surgical outcomes [19] . Elderly patients have been demonstrated to be associated with higher morbidity and mortality in patients undergoing total knee and hip arthroplasty [13][14][15]20] . For patients with increased age, more coexisting medical conditions, such as malnutrition, frailty and the functional status decrease with increasing age, may contribute to the poor postoperative outcome.…”
Section: Discussionmentioning
confidence: 99%